Industrial Safety in Readymade Garment Sector: A Developing Country Perspective - Ahmed, Jashim Uddin; Hossain, Tamima (Administration and Management Review, 2009)
Readymade Garment (RMG) sector has been playing an important role in the overall economic development of Bangladesh. In the post-quota globalized world, issues relating to social compliance have become increasingly important in the export-oriented RMG Sector. With the collapse of Savar Spectrum Sweater factory, the Phoenix Fabrics Mill Ltd., the fire at KTS Fabrics Mills and Chowdhury Knitwear Garments the industrial health and safety issues have been identified a burning issue in RMG sector and lots of pressure have been imposed on the industry proprietors as well as on the government regarding the safety of workers and their over all welfare. In this study an overview of the safety issues in RMG Industry of Bangladesh have been presented. We put forward the relevant factual cases to support our analysis of the industry’s safety scenario as a whole. Moreover, some of our thoughts and findings followed by a set of recommendations and conclusion are revealed at the end of this report. Administration and Management Review Vol. 21 No. 1, January 2009, Page 16-31